FEATURES OF THE REVISION OF THE TERMS OF THE AGREEMENT IN CONNECTION WITH A SIGNIFICANT CHANGE OF CIRCUMSTANCES - Kozhevnikovа Victoria (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: research consists in an exposure and decision of complex of the theoretical and practical problems related to conformities to law of revision of conditions of the civil legal agreement in connection with the substantial change of circumstances, improved conceptions of the modern understanding of substantial change of circumstances and her influence on actual realization by parties of conditions of the agreement (to the contract). Research methods: for realization of the marked aim, in the process of scientific research totality of methods of scientific cognition is used scientific and specially scientific methods became methodological basis of scientific work. Results: the found out positions of current civil legislation of Ukraine in relation to the normative order of establishment of conditions of the civil legal agreement (to the contract) and them actual modification if it be impossible implementation in connection with the substantial change of circumstances. Discussion: the article elucidates the scientific approaches to the legal category of a material change of circumstances in the course of fulfillment of the terms of an agreement (contract) by the parties. The author establishes that unavoidable circumstances may arise in contractual relations as grounds for modification or termination of an obligation due to an objectively determined (permanent or temporary) impossibility of its fulfillment, and in some cases, the factors identified herein significantly complicate, but do not make it impossible for the parties to fulfill their obligations in general, and therefore have, at most, the character of a case for the interested party, creating only a subjective impossibility of fulfillment of the obligation.